Western China: FDI opportunities & risks. - Goh, Thong Liang. (2008)
This report highlights the potential FDI investment opportunities and risks in Western China in view of the Western Development Strategy. Specifically, an in-depth analysis was done on Chongqing, Shaanxi and Sichuan.